2007
DOI: 10.1063/1.2719153
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of hole injection using ozone treated Ag nanodots dispersed on indium tin oxide anode for organic light emitting diodes

Abstract: The authors report the enhancement of hole injection using an indium tin oxide ͑ITO͒ anode covered with ultraviolet ͑UV͒ ozone-treated Ag nanodots for fac tris ͑2-phenylpyridine͒ iridium Ir͑ppy͒ 3-doped phosphorescent organic light-emitting diodes ͑OLEDs͒. X-ray photoelectron spectroscopy and UV-visible spectrometer analysis exhibit that UV-ozone treatment of the Ag nanodots dispersed on the ITO anode leads to formation of Ag 2 O nanodots with high work function and high transparency. Phosphorescent OLEDs fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 18 publications
(14 reference statements)
3
18
0
Order By: Relevance
“…The fairly strong C 1s peak corresponded to the existence of organic contamination on the ITO anode. The results are similar to the reported ones [24]. By comparing the ITO/V 2 O 5 case in Fig.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…The fairly strong C 1s peak corresponded to the existence of organic contamination on the ITO anode. The results are similar to the reported ones [24]. By comparing the ITO/V 2 O 5 case in Fig.…”
supporting
confidence: 80%
“…Using metal oxides with high work function, such as AgO x [8] and NiO x [9], as an interfacial layer between ITO and organic material has [11]. It has also been used as an efficient modification layer of ITO and (p-Si) anode to enhance hole injection [12], [13].…”
mentioning
confidence: 99%
“…Recently there has been considerable interest in the structural and electrical properties of ITO contact layers [4][5][6]. In this research, band structure characteristics of ITO layers are very important for analysing the contact potential of ITO electrodes and functional layers in devices [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…One method is to use various metal layers; Kim et al, reported that ozone-treated silver film on an ITO anode can enhance device performance [12]. Silver is frequently used as the electrode material in OLEDs [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%